Quantitative evaluation of sebum lipid components with nuclear magnetic resonance - Lora C. Robosky; Kimberly Wade; Dayna Woolson; John David Baker; Matthew L. Manning; Douglas A. Gage; Michael D. Reily (Journal of Lipid Research, 2008)
A NMR spectroscopic method is described that enables the quantitation of specific lipid classes and components, independent of fatty acid composition. We demonstrate this method for measuring cholesterol, squalene, and pools of sterol esters, wax esters (WEs), and triglyceride (TG) components in sebum and meibum. When 600 MHz NMR equipment is used in conjunction with highly sensitive cryogenically cooled probes, this method has adequate sensitivity, and for some applications, advantages over commonly used HPLC-evaporative light-scattering detection and mass spectrometry-based approaches. This method is shown to be useful for preclinical and clinical monitoring of the efficacy of sebum-reducing agents in animals and humans. In Syrian hamsters, 3% topical flutamide and 20 mg/kg oral isotretinoin reduced sterol esters by 18.7% and 30.0%, respectively, and reduced WEs by 32.9% and 31.8%, respectively, as measured in a punch biopsy of the ear. In a 72 patient clinical methodology study, the assay delivered reproducible and noninvasive measurements of WEs, cholesteryl esters, TGs, and squalene from Sebutape® skin blots. The quantitative results of sebum analysis obtained by the NMR method correlate well with those obtained with HPLC-based approaches. This approach may be broadly applicable to cases in which fatty acid-independent quantification of lipid classes is desired.